2018
DOI: 10.1002/jaba.454
|View full text |Cite
|
Sign up to set email alerts
|

Effects of delay fading and signals on self‐control choices by children

Abstract: The current study is a systematic replication and extension of work by Schweitzer & Sulzer-Azaroff (1988). The effects of delay fading alone and in combination with signals on choices between larger, delayed reinforcers and smaller, immediate reinforcers by four children with language deficits were examined. For one of the two children exposed to delay fading alone, larger reinforcers were selected at longer delays relative to the initial self-control assessment. For all four children, the delay-fading-plus-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
0
6
0
6
Order By: Relevance
“…Delay tolerance paradigms produce similar effects in children and adults. Multiple studies have shown that increasing the delay to the LL reward during the intervention phase increased LL choices in subsequent impulsive choice tasks in children with ADHD (Binder, Dixon, & Ghezzi, 2000; Neef, Bicard, & Endo, 2001), preschool aged typically developing children (Schweitzer & Sulzer-Azaroff, 1988), children with developmental disabilities (Vessells, Sy, Wilson, & Green, 2018), children and adults with severe behavior disorders (Fisher, Thompson, Hagopian, Bowman, & Krug, 2000), and adults with intellectual disabilities (Dixon et al, 1998; Dixon, Rehfeldt, & Randich, 2003). These improvements were observed after multiple sessions of training.…”
Section: Temporal Processes and Impulsivitymentioning
confidence: 99%
“…Delay tolerance paradigms produce similar effects in children and adults. Multiple studies have shown that increasing the delay to the LL reward during the intervention phase increased LL choices in subsequent impulsive choice tasks in children with ADHD (Binder, Dixon, & Ghezzi, 2000; Neef, Bicard, & Endo, 2001), preschool aged typically developing children (Schweitzer & Sulzer-Azaroff, 1988), children with developmental disabilities (Vessells, Sy, Wilson, & Green, 2018), children and adults with severe behavior disorders (Fisher, Thompson, Hagopian, Bowman, & Krug, 2000), and adults with intellectual disabilities (Dixon et al, 1998; Dixon, Rehfeldt, & Randich, 2003). These improvements were observed after multiple sessions of training.…”
Section: Temporal Processes and Impulsivitymentioning
confidence: 99%
“…Typically, individuals receive interventions with fading (progressively increasing or decreasing) SS or LL delays within an impulsive choice task. Exposure to delays increases LL choices in children with ADHD [40,41], children and adults with developmental and/or intellectual disabilities [42][43][44], children and adults with severe behavior disorders [45] as well as typically-developing children [28]. While some of these studies included female participants, the efficacy of the interventions in each sex was not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Intervention efficacy may be related to delay aversion (Sonuga‐Barke et al, 1992). Exposure to short delays may have enhanced the LL choice, as is seen with fading interventions (Logue & Mazur, 1981; Mazur & Logue, 1978; Vessells et al, 2018), while occasional long delays may have promoted delay tolerance. Because long delays were infrequent, rats had to occasionally wait for long delays in the context where they mostly waited for short delays.…”
Section: Discussionmentioning
confidence: 99%